Image evaluation system, image evaluation method and recording medium storing image evaluation program - Momoki, Yohei (2019)
Provided are an image evaluation system, as well as an image evaluation method, and recording medium storing an image evaluation program, in which when an image is selected from among multiple images, images are evaluated in such a manner that an image such as a scenic image or still-life image will be selected with little image bias. To achieve this, an individual image composition/subject matrix is found, the matrix comprising types of composition and types of subject included in an image. A total image composition/subject matrix is obtained by adding individual image composition/subject matrices regarding respective ones of multiple images. A composition evaluation matrix and a subject evaluation matrix are found from the total image composition/subject matrix. Image evaluation values regarding respective ones of the multiple images are calculated from a matrix product of the individual image composition/subject matrix, composition evaluation matrix and subject evaluation matrix.